Pengaruh Financial Knowledge, Financial Attitude, dan Self-Control terhadap Financial Management Behavior Mahasiswa di Kota Batam - Winny Winny; Risca Azmiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Financial management behavior reflects an individual's ability to manage personal finances through planning, monitoring, and evaluating the use of funds. For students, this skill is very important because they begin to manage their finances independently with limited income. This study aims to analyze the influence of financial knowledge, financial attitudes, and self-control on the financial management behavior of accounting students in Batam City.The method used is a quantitative approach with primary data from a structured questionnaire, analyzed through multiple linear regression. The results show that financial knowledge has a significant effect, so students with a good understanding are more effective at managing their finances. Financial attitudes are also significant, where positive attitudes encourage better planning and control.In addition, self-control has a significant effect because it helps regulate spending and maintain consistency in financial plans. Overall, these three variables are proven to significantly influence students' financial management behavior.